Evaluasi Dan Perbaikan Rancangan Antarmuka Pengguna Situs Web Jawa Timur Park Group Menggunakan Metode Goal-Directed Design (GDD) - Yudistira Maulana; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Jawa Timur Park Group is one of the recreational and learning attractions in Batu, East Java. Jawa Timur Park Group has a website that requires improvements in user interface, information structure and features such as online tickets and events. Goal-Directed Design method can provide a solution to produce a prototype that is suitable for the user's goals. Goal-Directed Design method has six phases within its application. It's research to get all needs and conditions desired by stakeholders and general users. Modeling that produces persona and describes stakeholders and users. Requirement that will produces context scenario and all needs. Framework that will produces an wireframe as the website interface. Refinement that will produce a high fidelity prototype. And Support that will test and evaluate the prototype that has been made. The final evaluation uses System Usability Scale (SUS) questionnaire. This final evaluation questionnaire gives an average score of 82.75 and get acceptable category of acceptability ranges, B category of grade scale, excellent category of adjective rating and get grade A of the percentile rank. So the result of the developed website had been good value and acceptable by users and stakeholders.